A RURAL FEMALE ADOLESCENT’S KNOWLEDGE OF ANEMIA - Utami, Kusniyati; Setyawati, Irni; Ariendha, Dian Soekmawaty Riezqy (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: Anemia is a condition of red blood cell count or hemoglobin count below the normal value of the reference value, anemia in adolescents will negatively affect growth, development, cognitive abilities and learning concentration, as well as increase susceptibility to infectious diseases. Anemia caused by the intake of foods that are low in iron, excessive blood loss that requires the formation of more red blood cells than usual. Some other factors that are suspected to influence the incidence of anemia in female adolescent are the knowledge of female adolescent about anemia itself. Objective: The purpose of this study was to identify knowledge of rural female adolescent about adolescent anemia. Methods: This research was a descriptive study with a survey method, located in East Penimbung Hamlet, West Lombok were conducted in July 2022. The population of the study is all of the female adolescent aged 11-24 years who not married, the sample subject of this study is 54 female adolescents were selected by non-probability sampling technique namely consecutive sampling with inclusion criteria, Female adolescent knowledge of anemia was identified by a closed-question questionnaire. The data analysis carried out by univariate analysis to describe the characteristics of respondents and adolescent knowledge about anemia. Result: The average age of female adolescents is 15-17 years (63%), 89% respondents had a thin nutritional status and 48% of respondents had an upper arm circumference less than 23.5 cm and 61% female adolescent has sufficient knowledge about anemia. Conclusion: The level of knowledge of adolescents about anemia is mostly moderate, health promotion from related parties about the definition of anemia, consequences and prevention of subsequent anemia needs to be carried out either through villages or schools.